Critical Discourse Analysis of Islamic Criminal Law Against Drug Crimes Committed by Children (Analysis of Palopo District Court Decision Number: 47/Pid.Sus.Anak/2016/PN.PLP) - Ismail; Muammar Arafat Yusmad; Takdir (Universitas Islam Negeri Palopo, 2025)
This study examines the application of Islamic criminal law principles in addressing drug-related offenses committed by minors through a critical discourse analysis of Palopo District Court Decision Number 47/Pid.Sus.Anak/2016/PN.PLP. The research explores the intersection between Islamic jurisprudence (fiqh) and Indonesia's contemporary juvenile justice system, particularly focusing on how Islamic legal principles are interpreted and applied in cases involving child offenders in drug-related crimes. The analysis reveals tensions between traditional Islamic criminal law approaches and modern restorative justice principles embodied in Indonesia's Law No. 11 of 2012 on the Juvenile Criminal Justice System. While Islamic law emphasizes the concept of ta'zir (discretionary punishment) and consideration of the offender's circumstances, Indonesian juvenile justice prioritizes rehabilitation, diversion mechanisms, and the child's best interests. The study demonstrates how judicial decisions attempt to reconcile these different legal frameworks, often favoring rehabilitative measures over punitive sanctions. The research employs critical discourse analysis methodology to examine legal language, judicial reasoning, and ideological underpinnings in the court decision. Findings indicate that judges navigate between Islamic legal principles—such as the consideration of mental capacity (ahliyyah) and the protective nature of Sharia toward minors—and secular legal requirements emphasizing restorative justice. The decision reflects Indonesia's pluralistic legal system, where Islamic law influences judicial interpretation while operating within the framework of national criminal law. The study concludes that contemporary Indonesian courts demonstrate flexibility in applying Islamic criminal law principles to juvenile drug cases, prioritizing rehabilitation and child protection over strict punitive measures. This approach aligns with both Islamic jurisprudential concepts of mercy (rahmah) and modern international standards for juvenile justice, suggesting a harmonious integration of religious and secular legal principles in addressing youth criminality.